Caffeine-related genes influence anxiety disorders in children and adults with ADHD. (January 2022) - Fraporti, Thailan Teles; Bandeira, Cibele Edom; Tovo-Rodrigues, Luciana; Martins-Silva, Thais; Hutz, Mara Helena; Rohde, Luis Augusto; Bau, Claiton Henrique Dotto; Grevet, Eugenio Horacio; da Silva, Bruna Santos; Rovaris, Diego Luiz; Dresch, Fabiane; Contini, Verônica; et al.
Abstract: Attention-deficit/hyperactivity disorder (ADHD) and anxiety disorders (AD) frequently co-occur, increasing morbidity and challenging treatment. Caffeine is a central nervous system stimulant and acts in the brain through adenosine receptors, influencing attention, alertness, and anxiety. In the present study, we performed a gene-set analysis to verify if genes related to caffeine response are associated with anxiety disorders in 240 children and 406 adults with ADHD. We demonstrated an association between the gene-set with AD in children (P = 0.0054) and with the number of anxiety disorders in adults (P = 0.0197). In order to test if this effect is a result of anxiety in general or is related to AD comorbid with ADHD, we evaluated the association between caffeine gene-set with AD in an adult control sample. The gene-set was neither associated with the AD presence (P = 0.3008) nor with the number of AD (P = 0.5594) in this control sample. We also test this gene set with ADHD (n = 55, 374) and AD (n = 18, 186) GWAS summary statistics, and we did not observe significant results with ADHD (P = 0.5587) or AD (P = 0.3930). These findings suggest the caffeine-related genes play a role in the etiology of an anxiety disorder phenotype present in children and adults with ADHD.